O meio ambiente no ensino técnico: uma análise de currículo e de projetos em uma instituição federal no Sul de Minas - Lima, Clarissa Cristina Pereira (2016)
This work analyzes the possibilities of approaching the environmental issue in curriculums of integrated technical programs, based on a case study conducted at the Centro Federal de Educação Tecnológica de Minas Gerais (CEFET-MG), Nepomuceno Unit. With this, we seek to contribute for the perception of the relevance of the environmental subject for technical programs, aiming at analyzing the insertion of Environmental Education into the curriculum of high school integrated technical education. The specific objectives are of identifying the existence of environmental subjects in the curricular structure and in projects developed at the CEFET -MG Nepomuceno; describe the subjects approached; analyze the curricular documents, referencing the basic formulations of the environmental field, such as Belgrade Charter, National Policy for Environmental Education and curricular guidelines for Environmental Education; and propose new educational actions regarding environmental issues in technical education. This work is divided into six chapters. The first exposes the motivations behind the study and introduces the researched subject. The second chapter presents the technical education, demonstrating how this mode of education was historically construed and how it is constituted nowadays, referencing the CEFET-MG. In elaborating this chapter, we analyzed the works of Cunha (1977 and 2000) and Fonseca (1961), in addition to document analysis of the Institutional Development Plan (PDI) of the CEFET -MG, and the National Curricular References of Technical Level Professional Education. The thir d chapter brings a reflection concerning curricular theory, establishing a relation between Technical Education and Environmental Education. The forth chapter proposes an analysis of Environmental Education, since its emergence as field of knowledge in the 1960’s until nowadays. For such, the main theoretical references used were Grün (1996), Loureiro (2012) and Carvalho (2008), who approach Environmental Education from a political and critical perspective. The research consisted of a case study, in which we conducted document analyses, searching for subjects on Environmental Education approached within a CEFET-MG unit, and described in the fifth chapter, dedicated to the methodology used in this work. The data were collected by means of document analysis, such as Program Projects, Discipline Plans and Project Reports. The sixth chapter shows the analysis of the researched documents, seeking to detail how Environmental Education is approached in a technical education institution. This chapter also points possible obstacles created by the technical education organization itself for approaching the subject, and proposes new Environmental Education practices for Technical Education. In conclusion, this work enlightened that the environmental subject is approached in Technical Education in a punctual manner, and is nearly always an extra -curricular activity.